Memahami Niat Beli Produk Mixue Pada Generasi Z Di Kota Bengkulu - Eleazar, Yosua; Hayadi, Ilsya (Universitas Islam Kadiri, 2023)
This study aims to understand the purchase intention of Mixue products in Generation Z in Bengkulu City. included in quantitative research using purposive sampling technique. The population of this study is generation z who live in Bengkulu city with an age range of 17 years - 26 years and have bought mixue products as many as 160 respondents. This research uses SEM-PLS version 4.0. The results of this study indicate that Viral marketing has a significant effect on purchase intention, Brand image has a significant effect on purchase intention, E-wom has no significant effect on purchase intention, Store atmosphere has a significant effect on purchase intention. can also conduct more in-depth research with the development of more comprehensive variables and more specific units of analysis. Future research can consider expanding the object of research so that the results obtained are more accurate than this study